Guideline for laboratory and chemical safety management - Kreunin, paweena; Nopparat, Pattama (Bulletin of Applied Sciences, 2022)
The effective management of chemical-based laboratories can help to reduce risks and prevent incidents that have the potential to occur in laboratories. This article’s objective is to enhance basic knowledge and understanding of laboratory and chemical safety management, as well as to raise awareness of workers who are involved in laboratory work. The content is divided into eight topics.i.e. 1) the importance of the development of safety management systems in chemical laboratories – related requirements and regulations, 2) the design of safety management systems in laboratories, 3) the control of hazardous chemicals, 4) the classification of hazardous chemicals, 5) chemical health risk assessment, 6) the management of hazardous chemicals, 7) the design and remodeling of laboratories for safety, and 8) the green laboratory management. The content is a guideline for the management system of green laboratories within the public and private sectors and educational institutions. However, organizations should have relevant and up-to-date training, knowledge-refresher trainings, and promote in-depth understandings on laboratory and chemical safety. In addition, organizations should continuously promote cultural awareness of safety within laboratories to achieve true safety. The organization’s drive will be an integral part that enhances the quality of laboratories, life, and environment in Thailand sustainably.